Effects of β-hydroxy-β-methylbutyrate treatment in different types of skeletal muscle of intact and septic rats - Kovarik, Miroslav; Muthny, Tomas; Sispera, Ludek; Holecek, Milan (Journal of physiology and biochemistry, 2010)
β-Hydroxy-β-methylbutyrate (HMB) is a leucine metabolite that may have a positive effect in protein catabolic conditions. Therefore, we hypothesized that HMB treatment could attenuate the sepsis-induced protein catabolic state. The aims of our study were to elucidate the effect of HMB in healthy and septic animals and to evaluate the differences in the action of HMB in different muscle types. Intact and septic (5 mg endotoxin/kg i.p.) rats were administered with HMB (0.5 g/kg/day) or saline. After 24 h, extensor digitorum longus (EDL) and soleus (SOL) muscles were isolated and used for determination of total and myofibrillar proteolysis, protein synthesis, leucine oxidation, activity of cathepsins B and L, chymotrypsin-like activity, and expression of α-subunits of proteasome. Our results indicate that the catabolic state induced by the endotoxin treatment was caused both by increase in protein breakdown (due to activation of proteasome system) and by attenuation of protein synthesis. The EDL (muscle composed of white, fast-twitch fibers) was more susceptible to these changes than the SOL (muscle composed of red, slow-twitch fibers). The HMB treatment had no effect in healthy animals but counteracted the changes in septic animals. The action of HMB was mediated by attenuation of proteasome activity and protein breakdown, not by stimulation of protein synthesis. More pronounced effect of the HMB treatment on myofibrillar proteolysis was observed in the SOL.
Keywords: kathepsin L; Proteasome Endopeptidase Complex; Male; Valerates; Oxygen; Rats, Wistar; kathepsin B; leucin; Lysosomes; proteasomový endopeptidasový komplex; sepse; Muscle, Skeletal; Leucine; mužské pohlaví; potkani Wistar; Cathepsin L; Sepsis; lyzozomy; kosterní svaly; krysa rodu Rattus; Time Factors; valeráty; Animals; kyslík; zvířata; Rats; časové faktory; Cathepsin B